Ophthalmomyiasis in humans - Chakraborti, C; Mukhopadhya, U; Mondal, M; Giri, D; Khan, M (Nepalese Journal of Ophthalmology, 2011)
Background: Ophthalmomyiasis in humans is a rare phenomenon. Objectives: To create awareness among the ophthalmologists regarding larval conjunctivitis. Cases: We report two cases of ophthalmomyiasis, which came to a tertiary care centre with features of unilateral acute catarrhal conjunctivitis. Observations: Fly larvae were detected on slit-lamp examination and removed after immobilizing them with topical 4 % lignocaine. Topical antibiotics and steroid drops were prescribed for 2 weeks. The samples were identified as Oestrous ovis by the entomology department of the Institute of Tropical Medicine, Kolkata. The signs and symptoms regressed within 48 hours. Conclusion: The ocular myiasis can manifest as a unilateral catarrhal conjunctivitis. Key words: Ophthalmomyiasis, Oestrous ovis, conjunctivitis DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5277 Nepal J Ophthalmol 2011; 3(2): 193-195